My Acquaintance with the CJE/RCE, 1988-1992 - Bruneau, William (Canadian Journal of Education/Revue canadienne de l'éducation, 2017)
In 1972, Canada’s academic societies in the humanities and social sciences met at Queen’s University. That year, Canadian education researchers organized the Canadian Society for the Study of Education (CSSE). They created a single, federated body, hoping it would play a vigorous role in the university. If all went well, the new organization would have an impact on the country and the wider worlds of educational thought and practice. Most of us thought that Canadian education researcher-writers were not being heard or seen as much as they should. We did not mean to hide our collective light under a bushel, yet European and American colleagues weren’t aware of our work. We wanted a new Canadian organizational base from which to operate. We hoped the CSSE would be that base.